Joint Effects of Principles-Based versus Rules-Based Standards and Auditor Type in Constraining Financial Managers’ Aggressive Reporting - Jamal, Karim; Tan, Hun-Tong (The Accounting Review, 2010)
ABSTRACT: Managers sometimes implement accounting standards (such as the lease standard) opportunistically to move debt off balance sheet. Regulators and standard-setters are considering the adoption of principles-based accounting standards to reduce such opportunism. We report the results of an experiment in which experienced financial managers, with incentives to structure a transaction off balance sheet, take a reporting position on how a lease is to be reported. We manipulate the type of accounting standards (principles-based, rules-based) and the type of auditor (principles-oriented, rules-oriented, or client-oriented). Results show that for a rules-based standard, auditor-type does not influence participants’ propensity to report the transaction off balance sheet. However, for a principles-based standard, auditor-type matters in that this propensity is lowest when the auditor is principles-oriented as opposed to rules- or client-oriented. Our results suggest that a move toward more principles-based standards is likely to result in improved financial reporting quality only when there is a corresponding shift in auditors’ mindsets toward being more principles-oriented.